Overexpression of AtOxR gene improves abiotic stresses tolerance and vitamin C content in Arabidopsis thaliana. Issue 1 (December 2016) - Bu, Yuanyuan; Sun, Bo; Zhou, Aimin; Zhang, Xinxin; Takano, Testuo; Liu, Shenkui
Abstract Background Abiotic stresses are serious threats to plant growth, productivity and result in crop loss worldwide, reducing average yields of most major crops. Although abiotic stresses might elicit different plant responses, most induce the accumulation of reactive oxygen species (ROS) in plant cells leads to oxidative damage. L-ascorbic acid (AsA, vitamin C) is known as an antioxidant and H2 O2 -scavenger that defends plants against abiotic stresses. In addition, vitamin C is also an important component of human nutrition that has to be obtained from different foods. Therefore, increasing the vitamin C content is important for improving abiotic stresses tolerance and nutrition quality in crops production. Results Here, we show that the expression ofAtOxR gene is response to multiple abiotic stresses (salt, osmotic, metal ion, and H2 O2 treatment) in both the leaves and roots ofArabidopsis . AtOxR protein was localized to the Endoplasmic Reticulum (ER) in yeast andArabidopsis cells by co-localization analysis with ER specific dye. AtOxR-overexpressing transgenicArabidopsis plants enhance the tolerance to abiotic stresses. Overexpression ofAtOxR gene resulted in AsA accumulation and decreased H2 O2 content in transgenic plants. Conclusions In this study, our results show that AtOxR responds to multiple abiotic stresses. Overexpressing AtOxR improves tolerance to abiotic stresses and increase vitamin C content inArabidopsis thaliana . AtOxR will be useful for the improvement of important crop plants through moleculer breeding.